Application of Box-Behnken design in the optimization of chitosan nanoparticles prepared by the ionic gelationultrasonication method and evaluation of dispersion stability - ÖZER ÖNDER, SETENAY; UĞURLU, TİMUÇİN (My University, 2024)
The main objective of this study was to optimize chitosan nanoparticles by exploring the relationship between design factors and experimental data through response surface methodology. A Box-Behnken design was employed, considering chitosan: tripolyphosphate ratio (X1), pH of the chitosan solution (X2), and ultrasonication amplitude (X3) as independent factors. Particle size, polydispersity index (PDI), and zeta potential served as the dependent variables. Nanoparticles were successfully prepared using a modified ionic gelation method incorporating an ultrasonic homogenizer and evaluated by models according to Box-Behnken Design. Surface plots were utilized to enhance the understanding of interactions between different variables. Results indicated that the chitosan ratio played the most significant role on both particle size and polydispersity, while the ultrasonic homogenizer amplitude predominantly influenced zeta potential. The models for particle size and polydispersity exhibited high accuracy (R², 0.9992 and 0.9955, respectively), whereas the zeta potential model demonstrated a lower R² value (0.7857) and lack of statistical significance. Comparison of predicted and actual data revealed larger error% values in the zeta potential model, exceeding the acceptable 15% threshold. Consequently, it was concluded that the ionic gelation-ultrasonic homogenizer technique, coupled with the Box-Behnken Design, is a rapid and effective approach for chitosan nanoparticle preparation and optimization. Additionally, aqueous dispersions of nanoparticles exhibited significant changes in particle size, polydispersity, and zeta potential values over one month at temperature and relative humidity conditions in accordance with ICH stability guidelines. This reinforced the recommendation that nanoparticles should be lyophilized and stored in a dry form. KEYWORDS: Chitosan; nanoparticle; Box-Behnken design; DoE, stability.
Keywords: Chitosan; nanoparticle; Box-Behnken design; DoE; stability